2022
DOI: 10.1172/jci157416
|View full text |Cite
|
Sign up to set email alerts
|

Searching for escape-resistant anti–SARS-CoV-2 neutralizing antibodies

Abstract: A major goal of SARS-CoV-2 vaccination is the induction of neutralizing antibodies (nAbs) capable of blocking infection by preventing interaction of the SARS-CoV-2 Spike protein with ACE2 on target cells. Cocktails of monoclonal nAbs can reduce the risk of severe disease if administered early in infection. However, multiple variants of concern (VOCs) have arisen during the pandemic that may escape from nAbs. In this issue of the JCI, Jia Zou, Li Li, and colleagues used yeast display libraries to identify mAbs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This implies that IgG antibody drugs with high specificity for ancestral SARS-CoV-2 spike proteins may not be effective against new mutant strains. Indeed, both vaccines inducing IgG antibodies and antibody cocktail therapies have been reported to have decreased efficacy against SARS-Cov-2 mutant strains [ 28 , 29 ]. On the other hand, secretory IgA is polymeric, and polymerization enhances cross-reactive properties, suggesting that mutations in the spike protein may have little effect on the binding of secretory IgA to SARS-CoV-2 targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that IgG antibody drugs with high specificity for ancestral SARS-CoV-2 spike proteins may not be effective against new mutant strains. Indeed, both vaccines inducing IgG antibodies and antibody cocktail therapies have been reported to have decreased efficacy against SARS-Cov-2 mutant strains [ 28 , 29 ]. On the other hand, secretory IgA is polymeric, and polymerization enhances cross-reactive properties, suggesting that mutations in the spike protein may have little effect on the binding of secretory IgA to SARS-CoV-2 targets.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, it may be that polymeric secretory IgA, with its low specificity and high cross-reactivity, recognizes similarities of the antigen that specific IgG cannot. Mahla and Dustin stated that in order to respond to viral mutations, the next generation of antibody cocktail therapy requires polymerization of antibodies [ 29 ], and recently, the ability of dimeric IgA to neutralize SARS-CoV-2 has been investigated [ 19 , 20 , 31 , 32 ]. In addition, it was reported that salivary IgA concentrations were low in COVID-19 patients and in those who had recovered, relative to asymptomatic controls negative for SARS-CoV-2 by polymerase chain reaction (PCR) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sotrovimab binds conserved epitopes of the RBD, which were used as a cocktail therapy for Omicron infection 160 . GlaxoSmithKline's VIR‐7831 (sotrovimab) and Regeneron monoclonal antibody cocktail have shown better efficacy 161,162 . VIR‐7831 (sotrovimab) and VIR‐7832 are dual‐acting monoclonal antibodies against spike‐in glycoproteins with neutralizing activity against Omicron variants 57 .…”
Section: Prophylaxis and Treatment Of Omicron Variantmentioning
confidence: 99%
“…160 GlaxoSmithKline's VIR-7831 (sotrovimab) and Regeneron monoclonal antibody cocktail have shown better efficacy. 161,162 VIR-7831 (sotrovimab) and VIR-7832 are dual-acting monoclonal antibodies against spike-in glycoproteins with neutralizing activity against Omicron variants. 57 Moreover, sotrovimab is more neutralizing against Omicron variants.…”
Section: Protective Effects Of Monoclonal Antibodies Against Omicron ...mentioning
confidence: 99%
“…Prior research on other respiratory viruses, including influenza A, established the importance of local and systemic IgA responses in acute viral infection and vaccination [7]. Mucosal IgA aids the local immune response in several ways, including preventing mucins from leaking, viruses from entering, merging with endosomal membranes within cells, and viruses from escaping host cells [7,56]. Vaccinated animals were more protected than others against viral multiplication, tissue damage, and lung inflammation [5].…”
Section: A Live Attenuated Vaccination Confers Superior Mucosal and S...mentioning
confidence: 99%